VD_FINDINFO HC / 2011 / 277 vom 26. April 2011 - VD Tribunal cantonal (2011)
RELATIONS PERSONNELLES, DISSOLUTION DU RÉGIME MATRIMONIAL, LIQUIDATION DU RÉGIME MATRIMONIAL | 204 al. 2 CC, 207 al. 1 CC, 214 CC, 273 al. 1 CC, 274 al. 2 CC